Optimal Solutions for Enhancing Teachers' Innovation through SITOREM Analysis - Gita Kencanawaty; Soewarto Hardhienata; Herfina Herfina (Attractive : Innovative Education Journal, 2025)
This study aims to determine the optimal solution based on existing solutions due to limitations in management resources. The method used in this study involves analyzing variables using Path Analysis, while indicators were analyzed using SITOREM (Scientific Identification Theory to Conduct Operations Research in Education Management). Based on the results of expert adjustments by two experts, the following indicator analysis results were obtained for each variable: There are 9 revised indicators in the following order: 1st Improving the Quality of Learning (21.6%), 2nd Changing Teaching Methods (19.6%), 3rd New Ideas (19.4%), 4th Paying Attention to Teachers’ Professional Goals (19.7%), 5th Working Conditions (19.4%), 6th Interpersonal Relationships (18.0%), 7th Applying Knowledge (22.3%), 8th Utilizing Organizational Support (19.5%), 9th Transferring Knowledge (18.7%). Meanwhile, the order of priority for indicators to be maintained or developed is as follows: 1st Technology Application (21.8%), 2nd Collaboration with Students and Colleagues (18.6%), 3rd Experimentation in Learning (18.4%), 4th Combining ideas into something new (21.2%), 5th Valuing teachers’ creative work (20.2%), 6th Exploring interests (20.0%), 7th Taking risks (19.2%), 8th Helping teachers overcome teaching challenges (21.2%), 9th Appreciating teachers’ creative work (19.9%), 10th Caring about teachers’ well-being (19.9%), 11th Appreciating teachers’ contributions to the development of learning methods (19.2%), 12th Self-development (22.0%), 13th Rewards (20.7%), 14th Achievement fulfillment (19.9%), 15th Acquiring knowledge (20.0%), 16th Receiving knowledge (19.5%).